(untitled) - Ismailova, S.I.; Yuldashev, O.S. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The study of functional state of thyroid gland and the structure of thyroid pathology for patients suffering from various forms of fibrotic-cystic disease was carried out. A total of 200 women with benign breast diseases were examined. A significant increase in the level of thyroid-stimulating hormone and antibodies to thyroperoxidase was observed in patients with pronounced mastopathy. Predominance of fibrotic component in breast tissue of patients with autoimmune thyroiditis and of cystic component of patients with iodine-deficient diseases of the thyroid gland was found. Correction of thyroid status in the presence of concurrent pathology was shown to be necessary. Conclusion: It can be considered that thyroid pathology can lead to dishormonal processes in the mammary glands. Clinical forms of mastopathy depend on the pathological process in the thyroid gland.